Comunicare per immagini: una questione di alfabeto (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2009)
This contribution presents a new hypothetical interpretation of the use of alphabetical signs during the first phase of the spread of writing in Etruria. Several pieces of the first half of the seventh century B.C. seem to show evidence that the form of the letters might be considered as a system of remarkable and recognisable signs with a function other than writing texts. This same function seems to continue in a specific use of the alphabetical sequence up to the end of the seventh century B.C. In the case of the spread of writing to other regions of the Italian peninsula, the alphabetical sequence seems to function as dynamic architecture that makes it possible to create multifaceted sequences of letters and sounds.This contribution examines groups of inscribed objects such as the red dishes (with the inscription spanti) and the kyathoi disseminated in Northern Etruria and present at Cerveteri, according to the same interpretation. These objects are considered as having a special relationship between sign and image in the framework of sacred ceremonies and as vehicles of long distance contacts.